The Influence of Backpack Weight and Hip Belt Tension on Movement and Loading in the Pelvis and Lower Limbs during Walking - Katja Oberhofer; Patrick D. Wettenschwiler; Navrag Singh; Stephen J. Ferguson; Simon Annaheim; Rene M. Rossi; Silvio Lorenzetti (Applied Bionics and Biomechanics)
The introduction of hip belts to backpacks has caused a shift of loading from the spine to the hips with reported improvements in musculoskeletal comfort. Yet the effects of different hip belt tensions on gait biomechanics remain largely unknown. The goal of this study was to assess the influence of backpack weight and hip belt tension on gait biomechanics. Data from optical motion capture and ground reaction forces (GRF) during walking were acquired in nine healthy male subjects (age 28.0 ± 3.9 years). Six configurations of a commercial backpack were analyzed, that is, 15 kg, 20 kg, and 25 kg loading with 30 N and 120 N hip belt tension. Joint ranges of motion (ROM), peak GRF, and joint moments during gait were analyzed for significant differences by repeated measures of ANOVA with Bonferroni post hoc comparison. Increased loading led to a significant reduction of knee flexion-extension ROM as well as pelvis rotational ROM. No statistically significant effect of hip belt tension magnitudes on gait dynamics was found at any backpack weight, yet there was a trend of increased pelvis ROM in the transverse plane with higher hip belt tension at 25 kg loading. Further research is needed to elucidate the optimum hip belt tension magnitudes for different loading weights to reduce the risks of injury especially with higher loading.